Odpowiedzi

2010-02-27T19:31:59+01:00
A)7x²-4x-6x²+4-x²+5x = x + 4

b)-2(3a-2b)-4a(2-3a+2b) = -6a + 4b -8a + 12a² - 8ab = -14a +12a² +4b -8ab

C)(4-x)(2x+5)-4 = 8x + 20 -2x² -5x -4 = -2x² +3x +16

d)(4-2x)(3x-3)-2x(3x+1)= 12x -12 -6x² +6x -6x² -2x = -12x² +16x -12
Najlepsza Odpowiedź!
2010-02-27T19:34:41+01:00
A)7x²-4x-6x²+4-x²+5x=7x²-6x²-x²-4x+5x+4=x+4

b)-2(3a-2b)-4a(2-3a+2b)=-6a+4b-8a+12a²-8ab=-14a+4b+12a²-8ab

C)(4-x)(2x+5)-4=8x+20-2x²-5x-4=3x-2x²+16

d)(4-2x)(3x-3)-2x(3x+1)=12x-12 -6x²+6x-6x²-2x=16x-12x²-12
2010-02-27T19:36:21+01:00
A) 7x² - 6x² - x² - 4x + 5x + 4
x + 4

b) -6a + 4b - 8a - 12a² - 8ab
-14a - 12a² + 4b - 8ab

c) 8x + 20 - 2x² - 5x - 4
-2x² + 3x = 16

d) 12x - 12 - 6x² + 6x - 6x² - 2x
16x - 12x² - 12